Beyond prevention: Unveiling the benefits of triple vaccination on COVID-19 severity and resource utilization in solid organ transplant recipients - Zhang, Jared R.; Johnson, John C.; Preble, Richard G.; Mujtaba, Muhammad; Lea, A. Scott; Stevenson, Heather L.; Kueht, Michael (Transplant immunology, 2024)
Despite the widespread reduction in COVID-19-related morbidity and mortality attributed to vaccination in the general population, vaccine efficacy in solid organ transplant recipients (SOTR) remains under-characterized. This study aimed to investigate clinically relevant outcomes on double and triple-vaccinated versus unvaccinated SOTR with COVID-19. A retrospective propensity score-matched cohort study was performed utilizing data from the US Collaborative Network Database within TriNetX (n = 117,905,631). We recruited vaccinated and unvaccinated (matched controls) SOTR with COVID-19 over two time periods to control for vaccine availability: December 2020 to October 2022 (bi-dose, double-dose vaccine effectiveness) and December 2020 to April 2023 (tri-dose, triple-dose vaccine effectiveness). A total of 42 factors associated with COVID-19 disease severity were controlled for including age, obesity, diabetes, and hypertension. We monitored 30-day outcomes including acute respiratory failure, intubation, and death following a diagnosis of COVID-19. Subjects were categorized into two cohorts based on the two time periods: bi-dose cohort (vaccinated, n = 462; unvaccinated, n = 20,998); tri-dose cohort (vaccinated, n = 517; unvaccinated, n = 23,061).Compared to unvaccinated SOTR, 30-day mortality was significantly lower for vaccinated subjects in both cohorts: tri-dose (2.0% vs 7.5%, HR = 0.22 [95% CI: 0.11, 0.46]); bi-dose (3.7% vs 8.2%, HR = 0.43 [95% CI: 0.24, 0.76]). Hospital admission rates were similar between bi-dose vaccinated and unvaccinated subjects (33.1% vs 28.6%, HR = 1.2 [95% CI: 0.95, 1.52]). In contrast, tri-dose vaccinated subjects had a significantly lower likelihood of hospital admission (29.4% vs 36.6%, HR = 0.74 [95% CI: 0.6, 0.91]). Intubation rates were significantly lower for triple-vaccinated- (2.3% vs 5.2%, p < 0.05), but not double-vaccinated subjects (3.0% vs 5.2%, p > 0.05). In solid organ transplant recipients with COVID-19, triple vaccination, but not double vaccination, against SARS-CoV-2 was associated with significantly less hospital resource utilization, decreased disease severity, and fewer short-term complications. These real-world data from extensively matched controls support the protective effects of COVID-19 vaccination with boosters in this vulnerable population. •Triple vaccination notably reduces mortality and hospitalization in SOTRs.•Bi-dose vaccination shows lesser protective effect compared to tri-dose.•Unveils increased DVT and hyperglycemia rates in vaccinated SOTRs.•Utilizes large-scale, real-world data from the US Collaborative Network.•Applies meticulous propensity score matching to ensure robust findings.